2013
DOI: 10.4317/medoral.18812
|View full text |Cite
|
Sign up to set email alerts
|

Case series of 589 tooth extractions in patients under bisphosphonates therapy. Proposal of a clinical protocol supported by Nd:YAG low-level laser therapy

Abstract: Objective: Trauma during dental surgery is a predisposing factor for bisphosphonates (BP)-related osteonecrosis of the jaws (BRONJ). However, about 40% of cases of BRONJ are not related to dental invasive procedures, being probably associated to endodontic or periodontal infections. Extraction of non-treatable teeth is considered a reliable choice, to improve symptoms and to reduce the risk of BRONJ. Here we report our experience of tooth extractions in patients under oral or intravenous BP therapy. Study Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 30 publications
4
69
0
5
Order By: Relevance
“…The laser light was used in a nonfocused way with a scanning method, 2 mm from the tissue, in five applications of 1 min each (power density 268.8 W/cm 2 , fluence 14.37 J/ cm 2 ). These parameters were selected on the basis of our clinical experience on the use of laser therapy in management of patients affected by or at risk for MRONJ [10,21]. Rats received the irradiation immediately after tooth extraction and then, under general anaesthesia, at days 2, 4, and 6 after surgery.…”
Section: Laser Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The laser light was used in a nonfocused way with a scanning method, 2 mm from the tissue, in five applications of 1 min each (power density 268.8 W/cm 2 , fluence 14.37 J/ cm 2 ). These parameters were selected on the basis of our clinical experience on the use of laser therapy in management of patients affected by or at risk for MRONJ [10,21]. Rats received the irradiation immediately after tooth extraction and then, under general anaesthesia, at days 2, 4, and 6 after surgery.…”
Section: Laser Therapymentioning
confidence: 99%
“…Two years later, Vescovi et al published a case series of 589 tooth extractions in patients under BP therapy using a clinical protocol supported by Nd:YAG laser therapy and concluded that it was effective in preventing BRONJ [10].…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24] The studies cited for (i) to (iv) in Table 4 are all case reports and have not been confirmed. In contrast, the effectiveness of teriparatide therapy (v) has been reported repeatedly.…”
Section: Discussionmentioning
confidence: 96%
“…She received several kinds of antimicrobials, but her BRONJ symptoms did not improve. Within two months of the start of the first Eti-RT, separation of sequestrum was observed, and so extraction 20.2±11.9 (7.6±5.0) 29±26 # Months after the first examination (and after the start of Eti-RT). * Sequestrum was separated before Eti-RT.…”
Section: )mentioning
confidence: 99%
“…59,[73][74][75][76][77][78][79] The studies cited for (i) to (iv) in Table 3 are all case reports and have not been confirmed. In contrast, the effectiveness of teriparatide therapy (v) has been repeatedly reported.…”
Section: Treatment Of Bronj: Eti As a Substitution Drug For N-bpsmentioning
confidence: 97%